2016
DOI: 10.1073/pnas.1521577113
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational association of mRNA encoding subunits of heteromeric ion channels

Abstract: Oligomers of homomeric voltage-gated potassium channels associate early in biogenesis as the nascent proteins emerge from the polysome. Less is known about how proteins emerging from different polysomes associate to form hetero-oligomeric channels. Here, we report that alternate mRNA transcripts encoding human ether-à-go-go-related gene (hERG) 1a and 1b subunits, which assemble to produce ion channels mediating cardiac repolarization, are physically associated during translation. We show that shRNA specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 45 publications
7
32
1
Order By: Relevance
“…Very recently, a phenomenon similar to the one observed here was reported for the two subunits of a heteromeric K ϩ channel expressed in cardiomyocytes, where silencing of one subunit caused a parallel decrease in the transcript for the other one (47). In that study, transcript stability was not investigated, but very interestingly, it was found that the two subunit mRNAs are physically associated and that this association is not dependent on the presence of the nascent-encoded proteins.…”
Section: Discussionsupporting
confidence: 79%
“…Very recently, a phenomenon similar to the one observed here was reported for the two subunits of a heteromeric K ϩ channel expressed in cardiomyocytes, where silencing of one subunit caused a parallel decrease in the transcript for the other one (47). In that study, transcript stability was not investigated, but very interestingly, it was found that the two subunit mRNAs are physically associated and that this association is not dependent on the presence of the nascent-encoded proteins.…”
Section: Discussionsupporting
confidence: 79%
“…For example, subunit expression can be regulated by co‐translational association with RNA (Liu et al . ).…”
Section: Cardiac K+ Channel Regulationmentioning
confidence: 97%
“…The mechanisms that determine the stoichiometric balance of different subunits are poorly understood, are often not recapitulated in heterologous expression systems, and may not be specified by amino acid sequence alone. J Physiol 595.7 For example, subunit expression can be regulated by co-translational association with RNA (Liu et al 2016).…”
Section: Questions Controversies or Challengesmentioning
confidence: 99%
“…2). Some potassium channels can begin to dimerize cotranslationally, before the subunits are released from the ribosome (Liu et al, 2016; Lu et al, 2001; Phartiyal et al, 2007; Robinson and Deutsch, 2005; Tu et al, 2000). The amino terminal domains of these channels, such as the T1 tetramerization domain of Kv channels, make the assembly process considerably faster and presumably also more efficient (Lu et al, 2001).…”
Section: Role Of Auxiliary Subunits In Controlling Functional Channelmentioning
confidence: 99%
“…Multiple channel subunits can be translated from the same mRNA molecule in the polyribosome complex resulting in a high local concentration of identical subunits. This will tend to favor the assembly of homo-dimers, especially for those channels that can begin dimerization before the subunits are released from the ribosome (Liu et al, 2016; Lu et al, 2001; Phartiyal et al, 2007; Robinson and Deutsch, 2005; Tu et al, 2000). Block of homo-dimerization by the binding of auxiliary subunits could facilitate the formation of heteromultimers.…”
Section: Role Of Auxiliary Subunits In Controlling Functional Channelmentioning
confidence: 99%